Adhesive composition and film-like sealing material

CN117625100BActive Publication Date: 2026-10-13SHIN ETSU CHEMICAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311106244.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-09-01
Filing Date
2023-08-30
Publication Date
2026-10-13
Estimated Expiration
2043-08-30

AI Technical Summary

Technical Problem

[0003]现有的环氧树脂与饱和烃型酸酐的粘合剂组合物虽然为低粘度且高透明性优异,但在可适用于钙钛矿型太阳能电池的低温下难以固化,因此在密封前后维持发电性能的能力较差

Benefits of technology

[0018]本发明的粘合剂组合物及膜状密封材料可用于粘合性、密合性、透明性粘合剂及粘合膜等,可广泛使用于涂料领域、电气领域、汽车领域、建筑·建材领域等。与现有的透明树脂相比,本发明的粘合剂组合物及膜状密封材料尤其显示低温固化性优异的特性。通过该特性,现有的透明树脂系所无法应对的低温固化性及密封前后的钙钛矿型太阳能电池的发电性能得到维持,因此可优选使用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117625100B_ABST
    Figure CN117625100B_ABST
Patent Text Reader

Abstract

The present invention provides a high-reliability epoxy resin-based adhesive composition and a film-shaped sealing material which are low in viscosity, low in curing temperature, high in adhesion, and maintain the power generation performance of a perovskite solar cell before and after sealing. The adhesive composition contains: (A) a reaction product of a bifunctional epoxy resin represented by general formula (2), a 3 or more functional epoxy resin represented by general formula (3), and a saturated anhydride represented by general formula (4); (B) a UV-sensitive reaction initiator; and (C) a dilution solvent, characterized in that the (A) component is a compound represented by general formula (1), the ratio of the total number of moles of the epoxy groups of the bifunctional epoxy resin and the 3 or more functional epoxy resin to the number of moles of the saturated anhydride is 1.30 to 3.00, and the number of moles of the bifunctional epoxy resin to the total number of moles of the bifunctional epoxy resin and the 3 or more functional epoxy resin is 0.001 to 0.15.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to adhesive compositions and film-like sealing materials. Background Technology

[0002] With the increasing demand for renewable energy in recent years, there is a growing need for transparent solar cells. Perovskite solar cells are considered as candidates for transparent solar cells. However, for commercial applications, there is a need for a film-type transparent solar cell that differs from monocrystalline or amorphous silicon solar cells and can be used for large-area installation on building walls or windows. To achieve this transparent, film-type solar cell, there is a need for an adhesive with low viscosity, low-temperature curing, high adhesion, and high reliability before and after sealing (Patent Document 1).

[0003] While existing epoxy resin and saturated hydrocarbon anhydride adhesive compositions offer excellent low viscosity and high transparency, they are difficult to cure at the low temperatures suitable for perovskite solar cells, resulting in poor ability to maintain power generation performance before and after sealing. Therefore, the power generation performance of pure epoxy resin and saturated hydrocarbon anhydride adhesive compositions is significantly reduced due to lack of curing, making them unsuitable as adhesive compositions or film-like sealing materials for sealing solar cells. Existing technical documents Patent documents

[0004] Patent Document 1: Japanese Patent Application Publication No. 2021-89946 Summary of the Invention The technical problem to be solved by the present invention

[0005] The present invention was made in view of the above circumstances, and its object is to provide an epoxy resin-based adhesive composition and a film-like sealing material with high reliability that has low viscosity, low temperature curing, high adhesion and maintains the power generation performance of perovskite solar cells before and after sealing. Technical means to solve technical problems

[0006] To address the aforementioned technical problems, the present invention provides an adhesive composition comprising: (A) a reaction product of a bifunctional epoxy resin of general formula (2), a trifunctional or higher epoxy resin of general formula (3), and a saturated acid anhydride of general formula (4); (B) a UV-sensitive reaction initiator; and (C) a diluent, wherein the adhesive composition is characterized in that... The component (A) is a compound represented by the following general formula (1). The amounts of the difunctional epoxy resin, the trifunctional or higher epoxy resin, and the saturated anhydride are such that the ratio of the total molar number of epoxy groups of the difunctional epoxy resin and the trifunctional or higher epoxy resin to the molar number of the saturated anhydride is 1.30 to 3.00, and the molar number of the difunctional epoxy resin is such that the ratio of the molar number of the difunctional epoxy resin and the trifunctional or higher epoxy resin to the total molar number of the difunctional epoxy resin and the trifunctional or higher epoxy resin is 0.001 to 0.15. In the formula, A is a saturated divalent hydrocarbon group; B is a group independently represented by general formula (1a) or general formula (1b); R2 is a substituted or unsubstituted divalent organic group, including aliphatic hydrocarbon groups, aromatic rings or heterocycles; R3 is a substituted or unsubstituted trivalent or higher organic group, including aliphatic hydrocarbon groups, aromatic rings or heterocycles; Z is a single bond or oxygen atom independently; k is an integer greater than 2; * represents an atomic bond; the order of repeating unit l and repeating unit m is arbitrary in the formula. In the formula, R2 and Z are the same as those mentioned above. In the formula, R3, Z, and k are the same as those mentioned above. In the formula, A is the same as the A mentioned above.

[0007] If it is such an adhesive composition, it is an epoxy resin-based adhesive composition with low viscosity, low temperature curing, high adhesion, and high reliability in maintaining the power generation performance of perovskite solar cells before and after sealing.

[0008] In this case, the reaction product is preferably a polymer formed by polymerizing the difunctional epoxy resin, the epoxy resin with more than three functions and the saturated acid anhydride, and the weight-average molecular weight of the polymer is 2000 to 20000.

[0009] If such an adhesive composition is used, the effects of the present invention described above become even more desirable.

[0010] Furthermore, in this invention, it is preferable to further contain the reaction product of general formula (5) formed by reacting an alkoxysilane compound of general formula (6) or a partial hydrolysate thereof with a compound of general formula (1) as component (A). In the formula, A, R2, R3, Z, k, and * are the same as A, R2, R3, Z, k, and * above; B' is each independently a group shown in general formula (5a) or general formula (5b); Z' is each independently a group of R4(OR5)2Si- or a group of a partially hydrolyzed alkoxysilane compound from general formula (6); R4 is a monovalent organic group containing vinyl, styryl, acryloyl, methacryloyl, amino, mercapto, urea, or isocyanate groups; and R5 is a monovalent organic group containing methyl, ethyl, propyl, or isopropyl groups.

[0011] If it is such an adhesive composition, it can achieve high adhesion to substrates such as glass.

[0012] Furthermore, in this invention, the bifunctional epoxy resin is preferably a BisA type epoxy resin as shown in the following general formula (2'), the epoxy resin with more than three functions is a triazine cyclic trifunctional epoxy resin as shown in the following general formula (3'), and the saturated acid anhydride is a saturated hydrocarbon acid anhydride as shown in the following general formula (4'). In the formula, n is an integer greater than or equal to 1.

[0013] If such an adhesive composition is used, the effects of the present invention described above become even more desirable.

[0014] Furthermore, the present invention provides a film-like sealing material formed from the dried product of the above-mentioned adhesive composition.

[0015] If such a film-like sealing material is used, it can provide good performance in maintaining the power generation performance of perovskite solar cells before and after sealing.

[0016] Preferably, the membrane sealing material further comprises a residual solvent, wherein the residual solvent is dimethylformamide and / or dimethyl sulfoxide, and the residual amount of the residual solvent in each unit mass of the membrane sealing material is less than 5000 ppm.

[0017] If the adhesive layer contains less than 5000 ppm of dimethylformamide or dimethyl sulfoxide as a residual solvent, it will not have a particularly adverse effect on the JV properties. Invention Effects

[0018] The adhesive composition and film-like sealing material of the present invention can be used in adhesives and adhesive films with good adhesion, sealing properties, and transparency, and can be widely used in the fields of coatings, electrical appliances, automobiles, and building materials. Compared with existing transparent resins, the adhesive composition and film-like sealing material of the present invention exhibit particularly excellent low-temperature curing properties. Through this property, the low-temperature curing performance and power generation performance of perovskite solar cells before and after sealing, which are unattainable by existing transparent resin systems, are maintained, making them a preferred choice. Detailed Implementation

[0019] To overcome the aforementioned shortcomings of existing materials, the inventors of this application conducted in-depth research, resulting in the achievement of high adhesion not only through the reaction of epoxy resin with saturated hydrocarbon anhydrides, but also through constructing a three-dimensional polymer structure containing, for example, a trifunctional epoxy resin containing a triazine ring and a trifunctional epoxy resin containing a triazine ring in a specified amount relative to BisA type epoxy resin. By blending to produce oligomers in an excess amount of epoxy relative to saturated hydrocarbon anhydrides, a film-like composition was obtained. Furthermore, by blending in an excess amount of epoxy relative to saturated hydrocarbon anhydrides within a specified range, a low-viscosity film-like composition was prepared. In addition, alkoxysilane partially hydrolyzed products were incorporated to achieve high adhesion to glass. It was found that, through the above methods, the epoxy resin adhesive composition (film-like adhesive composition) of the present invention possesses the characteristics of providing low viscosity, high adhesion, low-temperature curing, and maintaining the power generation performance of perovskite solar cells before and after sealing, thus completing the present invention.

[0020] That is, the present invention is an adhesive composition comprising: (A) a reaction product of a bifunctional epoxy resin of general formula (2) below, a trifunctional or higher epoxy resin of general formula (3) below, and a saturated acid anhydride of general formula (4) below; (B) a UV-sensitive reaction initiator; and (C) a diluent, wherein the adhesive composition is characterized in that... The component (A) is a compound represented by the following general formula (1). The amounts of the difunctional epoxy resin, the trifunctional or higher epoxy resin, and the saturated anhydride are such that the ratio of the total molar number of epoxy groups of the difunctional epoxy resin and the trifunctional or higher epoxy resin to the molar number of the saturated anhydride is 1.30 to 3.00, and the molar number of the difunctional epoxy resin is such that the ratio of the molar number of the difunctional epoxy resin and the trifunctional or higher epoxy resin to the total molar number of the difunctional epoxy resin and the trifunctional or higher epoxy resin is 0.001 to 0.15. In the formula, A is a saturated divalent hydrocarbon group; B is a group independently represented by general formula (1a) or general formula (1b); R2 is a substituted or unsubstituted divalent organic group, including aliphatic hydrocarbon group, aromatic ring or heterocycle; R3 is a substituted or unsubstituted trivalent or higher organic group, including aliphatic hydrocarbon group, aromatic ring or heterocycle; Z is a single bond or oxygen atom independently; k is an integer greater than 2; * is an atomic bond; the order of repeating unit l and repeating unit m is arbitrary in the formula. In the formula, R2 and Z are the same as those mentioned above. In the formula, R3, Z, and k are the same as those mentioned above. In the formula, A is the same as the A mentioned above.

[0021] The present invention will now be described in detail, but it is not limited thereto.

[0022] This invention relates to a highly reliable epoxy resin adhesive composition and a film-like sealing material that features low viscosity, low temperature curing, high adhesion, and maintains the power generation performance of perovskite solar cells before and after sealing.

[0023] The adhesive composition of the present invention comprises: (A) a reaction product of a specific difunctional epoxy resin, a trifunctional or higher epoxy resin, and a saturated anhydride; (B) a UV-sensitive reaction initiator; and (C) a diluent. The adhesive composition is characterized in that the amounts of the difunctional epoxy resin, the trifunctional or higher epoxy resin, and the saturated anhydride are such that the ratio of the total molar number of epoxy groups of the difunctional epoxy resin and the trifunctional or higher epoxy resin to the molar number of the saturated anhydride is 1.30 to 3.00, and the molar number of the difunctional epoxy resin is such that the ratio of the molar number of the difunctional epoxy resin to the total molar number of the trifunctional or higher epoxy resin is 0.001 to 0.15. In addition to components (A) to (C) above, other components may be included as needed. Furthermore, the adhesive composition of the present invention can also be formulated into a film (film-like adhesive composition). The composition of the adhesive composition of the present invention will be described below.

[0024] [(A) ingredient] (A) The reaction product of the bifunctional epoxy resin shown in the following general formula (2), the epoxy resin with more than three functions shown in the following general formula (3), and the saturated acid anhydride shown in the following general formula (4) is a compound shown in the following general formula (1).

[0025] In the above formulas, A represents a saturated divalent hydrocarbon group. B represents a group independently represented by formula (1a) or formula (1b). R2 represents a substituted or unsubstituted divalent organic group, including aliphatic hydrocarbon groups, aromatic rings, or heterocycles. R3 represents a substituted or unsubstituted trivalent or higher organic group, including aliphatic hydrocarbon groups, aromatic rings, or heterocycles. Z represents a single bond or an oxygen atom independently. k is an integer greater than 2. * represents an atomic bond. The order of repeating unit l and repeating unit m is arbitrary in the formula.

[0026] In the formula, R2 and Z are the same as those mentioned above. In the formula, R3, Z, and k are the same as those mentioned above. In the formula, A is the same as the A mentioned above.

[0027] Thus, the compound represented by general formula (1) is a reaction product of a bifunctional epoxy resin, a trifunctional or more functional epoxy resin and a saturated anhydride (saturated hydrocarbon anhydride), and has epoxy residues of bifunctional epoxy and trifunctional or more functional epoxy in its skeleton.

[0028] In the synthesis of component (A), the specific compound described later (bifunctional epoxy resin, trifunctional or higher epoxy resin, saturated anhydride) is reacted such that the total molar number of epoxy groups of the bifunctional epoxy resin and the trifunctional or higher epoxy resin is in a ratio of 1.30 to 3.00 to the molar number of the saturated anhydride, and the molar number of the bifunctional epoxy resin is in a ratio of 0.001 to 0.15 to the total molar number of the bifunctional epoxy resin and the trifunctional or higher epoxy resin. In general formula (1), l and m are numbers satisfying the above conditions.

[0029] <Dual-functional epoxy resin> The bifunctional epoxy resin used in the synthesis reaction of the compound represented by general formula (1) is represented by the following general formula (2). Wherein, R2 is a substituted or unsubstituted divalent organic group, including aliphatic hydrocarbon groups, aromatic rings, or heterocycles. Z is each independently a single bond or an oxygen atom.

[0030] The epoxy resin used in this invention as the difunctional epoxy resin (component of general formula (2)) is a compound having two epoxy groups in its molecule. In particular, the epoxy equivalent is preferably 50 to 5000 g / eq, more preferably 100 to 500 g / eq.

[0031] The weight-average molecular weight of the epoxy resin is typically less than 10,000, preferably 400 to 9,000, and more preferably 500 to 8,000. In addition, the weight-average molecular weight (Mw) is the weight-average molecular weight converted from standard polystyrene determined by gel permeation chromatography (GPC) (the same applies below).

[0032] Examples of such epoxy resins include diglycidyl ethers of bis(4-hydroxyphenyl)methane, 2,2'-bis(4-hydroxyphenyl)propane, or their halides, and condensation polymers of these compounds (so-called bisphenol F type epoxy resins, bisphenol A type epoxy resins, etc.); epoxides of dienes such as butadiene diepoxide and vinylcyclohexene dioxide; glycidyl ethers or polyglycidyl esters obtained by condensing 1,2-dihydroxybenzene, resorcinol, or other diphenols or diols with epichlorohydrin, such as diglycidyl ethers of resorcinol, 1,4-bis(2,3-epoxypropoxy)benzene, 4,4'-bis(2,3-epoxypropoxy)diphenyl ether, 1,4-bis(2,3-epoxypropoxy)cyclohexene, and bis(3,4-epoxy-6-methylcyclohexylmethyl)adipate. In addition, examples include epoxy phenolic varnishes (i.e., phenolic varnish-type epoxy resins) obtained by condensing phenolic varnish-type phenolic resins (such as phenolic varnish and cresol varnish) with epichlorohydrin; epoxidized polyolefins and epoxidized polybutadiene obtained by epoxidation using the peroxidation method; epoxy resins containing naphthalene rings; biphenyl-type epoxy resins; phenol aralkyl-type epoxy resins; biphenyl aralkyl-type epoxy resins; and binary epoxy resins such as cyclopentadiene-type epoxy resins.

[0033] Among them, the preferred resins as components of general formula (2) are bisphenol F type epoxy resin and bisphenol A type epoxy resin, which are liquid at room temperature.

[0034] Commercially available products can also be used as components of general formula (2). Examples of commercially available products include JER-1001 (manufactured by Mitsubishi Chemical Corporation), a BisA type epoxy resin.

[0035] These epoxy resins can be used alone or in combination of two or more.

[0036] <Epoxy resins with 3 or more functionalities> The epoxy resin with three or more functions used in the synthesis reaction of the compound represented by general formula (1) is represented by the following general formula (3). Wherein, R3 is a substituted or unsubstituted trivalent or more organic group, including aliphatic hydrocarbon groups, aromatic rings, or heterocycles. Z is each independently a single bond or an oxygen atom. k is an integer of 2 or more, preferably 2.

[0037] Examples of epoxy resins with three or more functionalities include glycidylamine type epoxy resins, heterocyclic epoxy resins, and aromatic or aliphatic epoxy resins with three or more functionalities. Examples of heterocyclic epoxy resins include epoxy resins having heterocycles with a triazine-like skeleton. Examples of aromatic epoxy resins with three or more functionalities include epoxy resins containing polyphenols, and examples of aliphatic epoxy resins with three or more functionalities include epoxy resins containing polyols.

[0038] (Glycidylamine type epoxy resin) Examples of glycidylamine type epoxy resins include tetraglycidyl diaminodiphenylmethane type epoxy resins, tetraglycidyl diaminodiphenyl sulfone type epoxy resins, tetraglycidyl diaminodiphenyl sulfone type epoxy resins, tetraglycidyl m-phenylenediamine, tetraglycidyl 1,3-diaminomethylcyclohexane, hydantoin type epoxy resins, and aminophenol type epoxy resins. Other specific examples of glycidylamine type epoxy resins include N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane (product name Epotohto YH-434L, Nippon Steel & Sumitomo Chemical Co., Ltd.), N,N,N',N'-tetraglycidyl-1,3-phenylenediamine (product name TETRAD-X, MITSUBISHI GAS CHEMICAL COMPANY, INC.), N,N-diglycidyl-4-glycidyloxyaniline, and N,N-diglycidyl-3-glycidyloxyaniline.

[0039] These epoxy resins can be used alone or in combination of two or more.

[0040] (Heterocyclic epoxy resin) As heterocyclic epoxy resins, triazine derivative epoxy resins, such as 1,3,5-triazine core derivative epoxy resins, are listed as preferred resins. In particular, epoxy resins containing isocyanurate rings exhibit excellent light resistance and electrical insulation properties. Compared to one isocyanurate ring, a divalent epoxy group is preferred, and a trivalent epoxy group is more preferred. Specific examples of such heterocyclic epoxy resins include triglycidyl isocyanurate (product name TEPIC-S, Nissan Chemical Corporation).

[0041] (Aromatic or aliphatic epoxy resins with 3 or more functions) Examples of trifunctional or higher-functional aromatic or aliphatic epoxy resins include epoxy phenolic varnishes (i.e., phenolic varnish-type epoxy resins) obtained by condensing phenolic varnish-type phenolic resins (such as phenolic varnishes and cresol varnishes with three or more epoxy groups in one molecule) with epichlorohydrin; epoxidized polyolefins and epoxidized polybutadiene obtained by epoxidation using the peroxidation method; naphthalene-containing epoxy resins; biphenyl-type epoxy resins; phenolic aralkyl-type epoxy resins; biphenyl aralkyl-type epoxy resins; and cyclopentadiene-type epoxy resins. Furthermore, as specific examples of aromatic epoxy resins with three or more functions, examples include tetrafunctional naphthalene-type epoxy resin (product name EPICLON HP-4700, DIC Corporation) and triphenylmethane-type epoxy resin (product name 1032H60, Mitsubishi Chemical Corporation).

[0042] <Saturated acid anhydrides> The saturated anhydride used in the synthesis of the compound represented by general formula (1) is represented by the following general formula (4). Wherein, A is a saturated divalent hydrocarbon group.

[0043] There are no particular limitations on the above-mentioned acid anhydrides used as epoxy resin curing agents, as long as they are saturated acid anhydrides. Examples of saturated acid anhydrides include succinic anhydride or anhydrides of methylsuccinic acid, ethylsuccinic acid, 2,2-dimethylsuccinic acid, 3-oxabicyclo[3,1,0]hexane-2,4-dione, tetradecylsuccinic acid, hexadecylsuccinic acid, 2-octadecylsuccinic acid, hexahydrophthalic acid, 3-methylhexahydrophthalic acid, 4-methylhexahydrophthalic acid, 3-ethylhexahydrophthalic acid, 4-ethylhexahydrophthalic acid, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, bicyclo[2,2,2]octane-2,3-dicarboxylic anhydride, norcantharidin, and cantharidin.

[0044] Commercially available products can also be used as the aforementioned saturated anhydrides. Examples of commercially available products include RIKACID MH (manufactured by New Japan Chemical Co., Ltd.).

[0045] These saturated anhydrides can be used alone or in combination of two or more.

[0046] In this invention, the compound ((A) component) represented by general formula (1) is the reaction product of the bifunctional epoxy resin represented by general formula (2), the epoxy resin with more than three functions represented by general formula (3), and the saturated acid anhydride represented by general formula (4). Furthermore, the amounts of the difunctional epoxy resin, the trifunctional or higher epoxy resin, and the saturated anhydride must be such that the ratio of the total number of moles of epoxy groups in the difunctional and trifunctional or higher epoxy resins to the number of moles of the saturated anhydride (moles of anhydride) (total number of moles of epoxy groups / moles of anhydride) is 1.30 to 3.00, and the moles of the difunctional epoxy resin are such that the ratio of the moles of the difunctional epoxy resin to the total number of moles of the difunctional and trifunctional or higher epoxy resins is 0.001 to 0.15 (difunctional epoxy resin ratio). By keeping the ratios of each component within this range, a highly reliable epoxy resin-based adhesive composition and film-like sealing material with low viscosity, low-temperature curing, high adhesion, and maintenance of the power generation performance of perovskite solar cells before and after sealing can be obtained. On the other hand, if the ratio of (total epoxy groups in moles) to (acid anhydride in moles) is less than 1.30, unreacted curing agent remains in the cured product, leading to deterioration in the moisture resistance of the resulting cured product or difficulty in solidifying at room temperature even after prepolymerization. This results in poor adhesive strength after curing and a significant reduction in power generation performance. Furthermore, if the ratio of (total epoxy groups in moles) to (acid anhydride in moles) is greater than 3.00, poor curing and reduced reliability may occur. If the ratio of bifunctional epoxy resin is less than 0.001 or greater than 0.15, a three-dimensional polymer structure cannot be constructed, resulting in poor adhesive strength after curing and a significant reduction in power generation performance.

[0047] To synthesize the aforementioned prepolymer, a method can be described as follows: mixing the aforementioned bifunctional epoxy resin, trifunctional or higher epoxy resin, and saturated anhydride at 50–200°C, preferably 60–120°C, more preferably 70–110°C, for 1–20 hours, preferably 2–15 hours, and then reacting the mixture. Alternatively, the target resin can be manufactured by adding the components described later, and the order of addition can be arbitrary. For example, when heating and mixing the bifunctional epoxy resin, trifunctional or higher epoxy resin, and saturated anhydride, a portion of the trifunctional or higher epoxy resin can first be heated and mixed with other components (first heating and mixing), and the remaining trifunctional or higher epoxy resin can be added to the resulting reactant and further heated and mixed (second heating and mixing) to obtain the target reaction product. In this case, the temperature, stirring time, and stirring method of the first heating and mixing and the second heating and mixing can be different. The aforementioned heating and mixing can also be carried out in the presence of the diluent described later.

[0048] Preferably, the reaction product contained in the adhesive composition of the present invention is a polymer formed by polymerizing a difunctional epoxy resin, a trifunctional or higher epoxy resin, and a saturated acid anhydride, and the weight-average molecular weight of the polymer is 2000 to 20000. If the weight-average molecular weight is 2000 or higher, the adhesive composition can be formed into a film; if it is 20000 or lower, the melt viscosity is suitable and the adhesive force is sufficient.

[0049] The weight-average molecular weight is the weight-average molecular weight converted from standard polystyrene as determined by GPC. The determination conditions for GPC are as follows. [Measurement Conditions] Development solvent: Tetrahydrofuran (THF) Flow rate: 0.6 mL / min Detector: Differential refractive index detector (RI) Column: TSKGuardcolomn SuperH-L TSKgelSuperH4000(6.0mm ID×15cm×1) TSKgelSuperH3000(6.0mm ID×15cm×1) TSKgelSuperH2000(6.0mm ID×15cm×2) (All manufactured by TOSOH CORPORATION) Column temperature: 40℃ Sample injection volume: 20 μL (0.5% by mass THF solution)

[0050] <Alkoxysilane compounds and partially hydrolyzed alkoxysilanes> In the adhesive composition of the present invention, it is preferable to further contain the reaction product of general formula (5), which is obtained by reacting an alkoxysilane compound of general formula (6) or a partial hydrolysate thereof with a compound of general formula (1), as the (A) component. In the formula, A, R2, R3, Z, k, and * are the same as those mentioned above. B' is each independently a group represented by general formula (5a) or general formula (5b). Z' is each independently a group of R4(OR5)2Si- or a group derived from a partially hydrolyzed alkoxysilane compound of general formula (6). R4 is a monovalent organic group containing vinyl, styryl, acryloyl, methacryloyl, amino, mercapto, urea, or isocyanate groups, and R5 is a monovalent organic group containing methyl, ethyl, propyl, or isopropyl groups.

[0051] Regarding adhesive compositions (or film adhesive compositions) containing a reaction product of general formula (5) obtained by reacting an alkoxysilane compound of general formula (6) or a partially hydrolyzed product thereof (hereinafter also referred to as "alkoxysilane compound, etc.") with a compound of general formula (1), high adhesion to glass and the like can be achieved because the alkoxysilane compound, etc., has a hydrolyzable alkoxysilyl group.

[0052] The alkoxysilane or alkoxysilane partially hydrolyzed condensate component is a partially hydrolyzed condensate synthesized by a hydrolysis condensation reaction of at least one or more alkoxysilanes represented by the above general formula (6), and is an alkoxysilane partially hydrolyzed condensate with a weight average molecular weight of 300 to 30,000 and a residual alkoxy content of 2 wt% to 50 wt%.

[0053] Partially hydrolyzed condensates synthesized by hydrolysis-condensation reactions of one or more alkoxysilanes containing general formula (6) are organosilicones with a three-dimensional network structure, mainly composed of trifunctional siloxane units. Besides partially hydrolyzed condensates directly synthesized by hydrolysis-condensation reactions of one or more alkoxysilanes containing general formula (6), they also include partially hydrolyzed condensates synthesized by further hydrolysis-condensation reactions of one or more alkoxysilanes containing general formula (6). The partially hydrolyzed condensates of alkoxysilanes of general formula (6) are not particularly limited as long as they contain trifunctional siloxane units.

[0054] Examples of partially hydrolyzed condensates of alkoxysilanes comprising the trifunctional alkoxysilanes shown in general formula (6) include (i) Wacker Asahikasei Silicone Co., Ltd., which manufactures: SY231 (containing methoxy, phenyl, and methyl (alkoxy equivalent 222)), SY550 (containing methoxy, phenyl, and methyl), SY300 (containing hydroxy, phenyl, and propyl (hydroxyl value 3 wt%)), SY409 (containing hydroxy, phenyl, and methyl (hydroxyl value 2.5 wt%)), SY430 (containing hydroxy and phenyl (hydroxyl value 5 wt%)), IC836 (containing hydroxy and phenyl (hydroxyl value 3.5 wt%)), and (ii) Shin-Etsu Chemical Co., Ltd., which manufactures: straight silicone. Resin): KR220L (solid), KR242A, KR271, KR282 (weight average molecular weight (Mw) = 100,000~200,000, containing hydroxyl groups (hydroxyl value 1% by weight)), KR300, KR311 (Mw = 6,000~10,000, containing hydroxyl groups (hydroxyl value 4.5% by weight)), organosilicon intermediates: KC89 (containing methoxy and methyl groups (methoxy content 45% by weight)), KR500 (packaged) Contains methoxy groups (methoxy content is 30% by weight)), KR212 (Mw = 2000-3000, contains hydroxyl, methyl, and phenyl (hydroxyl value is 5% by weight)), KR213 (contains methoxy, methyl, and phenyl (methoxy content is 22% by weight)), KR9218 (contains methoxy, methyl, and phenyl (methoxy content is 15% by weight)), KR251, KR400, KR255, KR216, KR152, (iii) Dow Corning Toray Co., Ltd.Manufacturing: Silicone resins: 804RESIN (phenyl methyl), 805RESIN (phenyl methyl), 806ARESIN (phenyl methyl), 840RESIN (phenyl methyl), SR2400 (methyl); Organosilicon intermediates: 3037INTERMEDIATE (Mw=1000, containing methoxy, phenyl, and methyl (methoxy content 18 wt%)), 3074INTERMEDIATE (Mw=1400, containing methoxy, phenyl, and methyl (methoxy content 17 wt%)), Z-6018 (Mw=2000, containing hydroxy, phenyl, and propyl (hydroxyl value 6 wt%)), 217FLAKE (Mw=2000, containing hydroxy and phenyl (hydroxyl value 6 wt%)), 220FLAKE (Mw=3000, containing hydroxy, phenyl, and methyl (hydroxyl value 6 wt%)). 6 wt%)), 233FLAKE (Mw=3000, containing hydroxyl, phenyl, and methyl (hydroxyl value 6 wt%)), 249FLAKE (Mw=3000, containing hydroxyl, phenyl, and methyl (hydroxyl value 6 wt%)), QP8-5314 (Mw=200, containing methoxy, phenyl, and methyl (methoxy content 42 wt%)), SR2402 (Mw=1500, containing methoxy and methyl (methoxy content 31 wt%)), AY42-161 (Mw=1500, containing methoxy and methyl (methoxy content 36 wt%)), AY42-162 (Mw=2500, containing methoxy and methyl (methoxy content 33 wt%)), AY42-163 (Mw=4500, containing methoxy and methyl (methoxy content 25 wt%)), (iv)TOAGOSEI CO.,LTD. manufactures: silsesquioxane derivatives, OX-SQ (containing oxetyl (functional equivalent: 263 g / eq)), OX-SQ-H (containing oxetyl (functional equivalent: 283 g / eq)), OX-SQSI-20 (containing oxetyl (functional equivalent: 262 g / eq)), AC-SQ (containing acryloyl (functional equivalent: 165 g / eq)), and alkoxysilane partially hydrolyzed condensates obtained by further hydrolyzing and condensing their alkoxysilane partially hydrolyzed condensates.

[0055] In the adhesive composition of the present invention, the compound represented by general formula (1) is preferably the reaction product of the following bifunctional epoxy resin, trifunctional epoxy resin and saturated acid anhydride. That is, preferably, the bifunctional epoxy resin is a BisA type epoxy resin represented by the following general formula (2'), the trifunctional or higher epoxy resin is a triazine cyclic trifunctional epoxy resin represented by the following general formula (3'), and the saturated anhydride is a saturated hydrocarbon anhydride represented by the following general formula (4'). Specifically, the BisA type epoxy resin can be JER-1001 (manufactured by Mitsubishi Chemical Corporation), the triazine cyclic trifunctional epoxy resin can be TEPIC-S (manufactured by Nissan Chemical Corporation), and the saturated hydrocarbon anhydride can be RIKACID MH (manufactured by New Japan Chemical Co., Ltd.).

[0056] In the formula, n is an integer greater than or equal to 1.

[0057] [(B) Component] The adhesive composition of the present invention contains a UV-sensitive reaction initiator as component (B). In this invention, a UV-sensitive reaction initiator (photocationic polymerization initiator) is required, which is a compound that initiates the polymerization of resin by light. There are no particular limitations on the type of compound that has this function; any compound can be used. A preferred example of a UV-sensitive reaction initiator is an onium salt having the structure shown in formula (7). This onium salt is a compound that undergoes a photoreaction and releases a Lewis acid. {R1 a R2 b R3 c R4 d Y} m+ {MX n+m} m- (7)

[0058] In formula (7), the cation is an onium ion, Y is S, Se, Te, P, As, Sb, Bi, O, I, Br, Cl or N2 (diazo group), R1, R2, R3 and R4 are the same or different organic groups, and a, b, c and d are integers from 0 to 3 and (a+b+c+d) equals the valence of Y. Examples of organic groups that can be represented as R1 to R4 include aryl groups such as phenyl, biphenyl, and naphthyl, aryl groups that are mono- or poly-substituted by C1 to C18 alkyl groups, phenoxyphenyl, and phenylthiophenyl.

[0059] M represents the constituent of the halide complex {MX} n+mThe central atom of} is a metal or metalloid, such as B, P, As, Sb, Fe, Sn, Bi, Al, Ca, In, Ti, Zn, Sc, V, Cr, Mn, Co, etc. X is a halogen atom such as F, Cl, Br, etc. m is the net charge of the halide complex ion, and n is the valence of M.

[0060] In formula (7), specific examples of ononium ions include diphenyliodonium, 4-methoxydiphenyliodonium, bis(4-methylphenyl)iodonium, bis(4-tert-butylphenyl)iodonium, bis(dodecylphenyl)iodonium, triphenylsulfonium, diphenyl-4-thiophenoxyphenylsulfonium, bis{4-(diphenylsulfonium)-phenyl}sulfide, bis{4-(di(4-(2-hydroxyethyl)phenyl)sulfonium)-phenyl}sulfide, η 5 -2,4-(cyclopentadiphenyl){1,2,3,4,5,6-η-(methylethyl)benzene}-iron(1+), etc.

[0061] In formula (7), specific examples of anions include tetrafluoroborate, hexafluorophosphate, hexafluoroantimonate, hexafluoroarsenate, and hexachloroantimonate. These UV-sensitive reaction initiators can be used alone or in combination of two or more.

[0062] As an initiator for UV-sensitive reactions, commercially available products can be used, such as CPI-300 manufactured by San-Apro Ltd.

[0063] Furthermore, these UV-sensitive reaction initiators are preferably added in the range of 0.1% to 10% by mass of the total organic components, and particularly preferably in the range of 1% to 3% by mass of the total organic components. If the amount added is 0.1% by mass or more, the curing properties are good; if it is 10% by mass or less, the curing properties are excellent and the shelf life is good.

[0064] [(C) Component] The adhesive composition of the present invention contains a diluent solvent as component (C). Organic solvents are typically used as diluents. Examples of organic solvents include ketone solvents such as acetone, methyl ethyl ketone (hereinafter also referred to as "MEK"), and cyclohexanone; acetate solvents such as ethyl acetate, butyl acetate, acetic acid cellosolve, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitol solvents such as cellosolve and butyl carbitol; aromatic hydrocarbon solvents such as toluene and xylene; aromatic ether solvents such as anisole; amide solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; and aromatic mixed solvents such as naphtha. Examples of aromatic mixed solvents include "SWASOL" (manufactured by Maruzen Petrochemical Co., Ltd., trade name) and "Ipsol" (manufactured by Idemitsu Kosan Co., Ltd., trade name). A single solvent can be used, or two or more solvents can be used in any ratio.

[0065] [Other ingredients] Depending on other requirements, the adhesive composition of the present invention may also be incorporated with alkoxysilane compounds, heat-curing catalysts, inorganic oxide particles, antioxidants, surfactants, storage stabilizers, leveling agents, light stabilizers, etc.

[0066] [Characteristics of the adhesive composition] (Melt viscosity) The melt viscosity of the adhesive composition is preferably 5 to 500 mPa·s. If the melt viscosity is below 500 mPa·s, the adhesion to the perovskite solar cell is sufficient. If the melt viscosity is above 5 mPa·s, when attaching it to the perovskite solar cell using rollers or the like, it is easy to expel air located in the recesses and voids are less likely to form. In addition, the melt viscosity can be measured, for example, using a rheometer (HAAKE MARS II (manufactured by EKO INSTRUMENTS CO.,LTD.)) with a gap of 500 μm, a sample diameter of 8 mm, a heating rate of 10 °C / min, and a frequency of 1 Hz, within the range of 25 °C to 200 °C.

[0067] (Curing temperature) The preferred curing temperature for the adhesive composition is 60°C to 120°C. Below 120°C, the perovskite layer will not be damaged, and the power generation efficiency is sufficient. Above 60°C, the adhesive composition (film-like adhesive composition, etc.) can be stored at room temperature without refrigeration or freezing. If condensation occurs in the (film-like) adhesive composition due to refrigeration or freezing, the perovskite layer will dissolve; however, this problem does not occur with the aforementioned adhesive composition.

[0068] [Membrane sealing material] The film-like sealing material of the present invention is formed from the dried solid of the above-described adhesive composition, obtained by evaporating the diluent from the adhesive composition of the present invention. The film-like sealing material of this invention can be used in adhesives, sealants, and transparent adhesives and films, and can be widely used in the coatings, electrical, automotive, and building materials industries. Compared with existing transparent resins, the film-like sealing material of this invention exhibits particularly excellent low-temperature curing properties. Through this property, the low-temperature curing performance and power generation performance of perovskite solar cells before and after sealing, which are unattainable with existing transparent resin systems, are maintained, making it a preferred choice.

[0069] (Method for manufacturing membrane sealing materials) The film-like sealing material can be manufactured by a manufacturing method including the step of forming a sealing material layer on a support. The sealing material layer can be formed, for example, by a method including the steps of: preparing an adhesive composition (varnish) containing a sealing material (adhesive) and a solvent; applying the varnish to the support; and drying (evaporating) the applied varnish. Membrane sealing materials can be manufactured, for example, in the following ways. A photoacid-generating agent (UV-sensitive reaction initiator) was added to a 50% anisole varnish of the above-mentioned epoxy resin to obtain an epoxy resin anisole solution. Using a bar coater, this epoxy resin anisole solution was applied to a peelable PET film that had undergone surface treatment with a silicone-based release agent. The PET film coated with the epoxy resin adhesive was dried (evaporated) using a dryer to obtain an epoxy film-like sealing material with an adhesive layer of a specified thickness.

[0070] The varnish can be dried using methods such as heating or hot air blowing. There are no particular limitations on the drying conditions; the temperature can be, for example, 50°C to 100°C. Furthermore, the drying time is preferably 1 minute or more, more preferably 3 minutes or more, preferably 60 minutes or less, and more preferably 15 minutes or less. After the varnish is applied to the support, it is allowed to dry, thereby removing the solvent (evaporation), resulting in a sealing material layer on the support.

[0071] Depending on the requirements, the manufacturing method of the film-like sealing material may also include a step of heating the sealing material layer. Heating allows the reactive groups contained in the sealing material to react, thus enabling reactions such as crosslinking and polymerization to proceed to an appropriate extent, thereby increasing the hardness of the sealing material layer. This heating is suitable for the use of adhesive-type sealing materials. It is particularly preferred when using adhesive-type sealing materials containing components with reactive groups such as anhydride groups and epoxy groups. This pre-sealing heating prevents thermal degradation of the components contained in the object being sealed. There are no particular limitations on the heating conditions. The heating temperature is preferably 50°C to 200°C, more preferably 100°C to 180°C, and even more preferably 120°C to 160°C. The heating time is preferably 15 minutes to 120 minutes, more preferably 30 minutes to 100 minutes.

[0072] Depending on the requirements, the manufacturing method of the film-like sealing material may also include a step of setting a protective film. The protective film can be set, for example, by bonding a protective film to the sealing material layer. When heating the sealing material layer, the protective film can be set before or after heating the sealing material layer.

[0073] The film-like sealing material may further contain residual solvents. Considering the characteristics of the sealing material, the residual solvent in the film-like sealing material is preferably minimal. The solvents listed above as diluents may become residual solvents. The residual amount of residual solvent in each unit mass of film-like sealing material is preferably less than 5000 ppm, more preferably less than 3000 ppm, and particularly preferably less than 1000 ppm. If the residual solvent is within the above range, it will not affect the JV characteristics of the perovskite solar cell. The preferred film-like sealing material further comprises a residual solvent, wherein the residual solvent is dimethylformamide (DMF) or dimethyl sulfoxide (DMSO), and the residual amount of the residual solvent in each unit mass of the film-like sealing material is less than 5000 ppm. When less than 5000 ppm of DMF or DMSO is included as a residual solvent in the adhesive layer, it does not have a particularly adverse effect on the JV characteristics.

[0074] (Instructions for using membrane sealing materials) The film-like sealing material can be used for sealing objects such as perovskite layers and electrodes. Sealing methods using film-like sealing materials typically involve laminating a layer of the sealing material onto the object to be sealed. When the film-like sealing material has a protective film, the lamination is usually performed after the protective film is peeled off. The lamination method can be batch-type or continuous using rollers.

[0075] Typically, through lamination, a sealing material layer and a support can be sequentially applied to the object to be sealed. Therefore, the laminated object may be covered by the sealing material layer and the support. In sealing methods using film-like sealing materials, it is possible to achieve a state where the object to be sealed is covered by the sealing material layer and the support without peeling off the support. In this state, since the object to be sealed is sealed not only by the sealing material layer but also by the support, moisture penetration can be effectively suppressed. For example, when using a film-like sealing material having a support with high moisture permeability, such as a support with a barrier layer or a support with a metal foil, it is preferable to perform the sealing using the sealing material layer and the support as described above.

[0076] Sealing methods using film-like sealing materials can, for example, involve peeling off the support after lamination to obtain a state where the object to be sealed is covered by a layer of sealing material. Even in this state, the penetration of moisture can be effectively suppressed by the sealing material layer that seals the object. For example, when using a film-like sealing material that does not have high moisture permeability resistance, such as a support without a barrier layer or a support without a metal foil, it is preferable to perform sealing using a layer of sealing material as described above.

[0077] Sealing methods using membrane-like sealing materials can, for example, further include providing a sealing substrate. Particularly when peeling off the support as described above, it is preferable to provide a suitable sealing substrate on the surface of the sealing material layer exposed due to the peeling of the support. As such a sealing substrate, for example, the same membrane as the support described above can be used, or rigid plates such as glass plates, metal plates, or steel plates can be used. By providing a sealing substrate, the penetration of moisture can be further effectively suppressed.

[0078] Sealing methods using film-like sealing materials can also include, for example, curing the sealing material layer after lamination. Typically, this is achieved by applying heat to the sealing material layer, causing the reactive groups contained within the sealing material to undergo cross-linking and polymerization reactions, thus thermosetting the sealing material layer. This improves the adhesion between the object being sealed and the sealing material, or increases the mechanical strength of the sealing material layer, thereby enhancing the sealing performance provided by the sealing material. Therefore, it is particularly effective in inhibiting the penetration of moisture and the leakage of lead. This post-lamination thermosetting method is suitable for applications using thermosetting sealing materials.

[0079] During the heat curing process, the sealing material layer is typically heated using a suitable heat treatment apparatus. Examples of such heat treatment apparatus include hot air circulating ovens, infrared heaters, hot air guns, and high-frequency induction heating devices. Alternatively, the sealing material layer can be heated by pressing a heating tool against it. From the perspective of improving the adhesion between the sealed object and the sealing material layer, the curing temperature is preferably 50°C or higher, more preferably 55°C or higher, and particularly preferably 60°C or higher. Furthermore, from the perspective of suppressing the thermal degradation of the components contained in the sealed object, the curing temperature is preferably 150°C or lower, more preferably 100°C or lower, and even more preferably 80°C or lower. The curing time is preferably 10 minutes or more, more preferably 20 minutes or more.

[0080] Any of the sealing methods described above can achieve a seal using a layer of sealing material. Therefore, when the object being sealed includes a lead-containing part such as a perovskite layer, it is possible not only to prevent moisture from penetrating into the lead-containing part, but also to prevent lead from leaking out of the lead-containing part.

[0081] As described below, the adhesive composition and film-like sealing material of the present invention can be photocured, thus eliminating the need for heating for curing (e.g., 60-120°C / 60 seconds). However, heat may be applied as needed to transfer the adhesive composition and film-like sealing material to a substrate (glass, etc.). Applying heat softens the material, allowing it to adhere tightly to the substrate (glass, etc.). Afterward, the temperature can be reduced to room temperature and the support film can be peeled off. The transfer temperature to the substrate is, for example, 60-120°C, preferably 80-100°C. The transfer time is 10-180 seconds, preferably 30-120 seconds. Curing can then be performed by light irradiation.

[0082] The adhesive composition and film-like sealing material of the present invention contain a UV-sensitive reaction initiator and can be photocured. For example, curing can be performed even at low temperatures around room temperature (25°C) by light irradiation. The photocuring conditions can be set according to the composition of the UV-sensitive reaction initiator and other components, for example, by using 460 mW / cm². 2 3000mJ / cm 2 Low-temperature curing can be achieved by irradiation with 365nm ultraviolet light. Irradiation conditions for photocuring include, for example, 200-3000mW / cm². 2 Preferably 300-1000mW / cm 2 .

[0083] The adhesive composition of the present invention cures with the film-like sealing material at low temperatures and exhibits good adhesion (adhesive strength). The adhesive strength can be evaluated in the following manner. First, prepare the adhesive composition (epoxy resin composition). Apply the epoxy resin composition to a 50 μm thick PET film (LS-2 manufactured by NIPPA Co., Ltd.) with a release agent to a thickness of 20 μm. Dry at 100°C for 10 minutes to evaporate the solvent, obtaining a two-layer film of PET-epoxy resin composition. Next, cover the alumina substrate with the epoxy resin composition side of the two-layer film facing the alumina substrate. Use a vacuum laminator to apply pressure (0.1 atm) while heating (60-120°C, 60 seconds each time) to ensure a tight bond between the epoxy resin composition and the alumina substrate. After cooling to room temperature, peel off the PET film to expose the epoxy resin composition layer. Five glass slides with sides of 5*5*1mm were placed on the epoxy resin composition layer, and then irradiated with ultraviolet light (365nm, 460mW / cm²). 2 This process is used to cure the material and create an adhesion test piece. The adhesion test piece is then tested using a weld strength tester (DageSeries4000Bondtester, test speed: 200 μm / s, test height: 10.0 μm, test temperature: 25℃) to measure the adhesion force (adhesion strength) at the time of cutting. Example

[0084] The present invention will be specifically described below with examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, parts represent parts by mass. Furthermore, in the synthesis examples, "(moles of total epoxy groups) / (moles of acid anhydride)" is the ratio of the total moles of epoxy groups in the difunctional epoxy resin and the trifunctional or higher epoxy resin (moles of total epoxy groups) to the moles of the saturated acid anhydride (moles of acid anhydride), and "difunctional epoxy resin ratio" is the value of (moles of difunctional epoxy resin) / [(moles of difunctional epoxy resin) + (moles of trifunctional or higher epoxy resin)].

[0085] (Examples 1-3, Comparative Example 1) [Synthesis example 1] A 1L separable flask equipped with a 25ml water receiver connected to a reflux condenser, a thermometer, and a stirrer, was filled with 19.70 parts of BisA type epoxy resin JER-1001 (manufactured by Mitsubishi Chemical Corporation), 31.89 parts of triazine cyclic trifunctional epoxy resin TEPIC-S (manufactured by Nissan Chemical Corporation), and 48.41 parts of RIKACID MH (manufactured by New Japan Chemical Co., Ltd.). The mixture was stirred at 90°C for 150 minutes to synthesize an epoxy-rich polymer. 100 parts of anisole were then added to prepare an epoxy anisole solution. The ratio of total epoxy groups to acid anhydrides was 1.27, and the ratio of bifunctional epoxy resins was 0.17.

[0086] [Synthesis example 2] To a 1L separable flask equipped with a 25ml water receiver connected to a reflux condenser, a thermometer, and a stirrer, add 1.45 parts of BisA type epoxy resin JER-1001 (manufactured by Mitsubishi Chemical Corporation), 30.27 parts of triazine cyclic trifunctional epoxy resin TEPIC-S (manufactured by Nissan Chemical Corporation), and 48.91 parts of RIKACID MH (manufactured by New Japan Chemical Co., Ltd.), and stir for 150 minutes at 90°C, thereby synthesizing an epoxy-rich polymer. Then, add another 19.37 parts of TEPIC-S (manufactured by Nissan Chemical Corporation), followed by 100 parts of anisole to prepare an epoxy anisole solution. The ratio of (total moles of epoxy groups) to (moles of acid anhydride) is 1.73, and the ratio of bifunctional epoxy resin is 0.096.

[0087] [Synthesis example 3] 1.45 parts of BisA type epoxy resin JER-1001 (manufactured by Mitsubishi Chemical Corporation), 49.64 parts of triazine cyclic trifunctional epoxy resin TEPIC-S (manufactured by Nissan Chemical Corporation), and 48.91 parts of RIKACID MH (manufactured by New Japan Chemical Co., Ltd.) were added to a 1L separable flask equipped with a 25ml water receiver connected to a reflux condenser, a thermometer, and a stirrer. The mixture was stirred at 90°C for 150 minutes to synthesize an epoxy-rich polymer. Add 19.37 parts of TEPIC-S (manufactured by Nissan Chemical Corporation), followed by 100 parts of anisole. Then, add 0.3 parts of KBM-803 (3-mercaptopropyltrimethoxysilane: manufactured by Shin-Etsu Chemical Co., Ltd.) to the epoxy-rich polymer. Stir at 75°C for 120 minutes to synthesize an epoxy-rich polymer with added alkoxysilane. Add 100 parts of anisole to prepare an epoxy anisole solution. The ratio of (total epoxy groups) to (acid anhydride) is 2.41, and the bifunctional epoxy resin ratio is 0.069.

[0088] [Production example 1] Perovskite solar cells are fabricated using the method described below. [MAPbI3·DMF complex] A solution containing PbI2 (2.305 g, 5.0 mmol) and methylammonium iodide (MAI; CH3NH3I; 795 mg, 5.0 mmol) dissolved in dimethylformamide (equivalent to DMF; 5.0 mL, MAPbI3; 1.0 M) was added to a screw-top tube. A few drops of DMF were allowed to flow along the tube wall and remain on top of the solution as a buffer layer. Toluene (a poor solvent) was slowly added on top, resulting in a 1:1 volume ratio of DMF to poor solvent. The container was capped and allowed to stand at room temperature. After approximately one day, the solvent diffused, forming colorless needle-like crystals. The crystals were filtered and collected, then dried under reduced pressure at room temperature for 20 minutes to obtain 3.167 g (94% yield) of needle-like crystals. 200 μL (for each 2.5 cm square electrode) of a 1:1 molar ratio solution of the DMF solution (prepared before filtration and drying) containing the crystals obtained above was dissolved in MAI to obtain a 1.55 M DMF solution, which was then spin-coated onto a mesoporous TiO2 layer. Three seconds before the end of the spin-coating process, 450 μL of toluene was added over two seconds. The resulting transparent film was immediately heated below 100 °C for 30 minutes, followed by annealing at 100 °C for 30 minutes, thereby obtaining high-purity MAPbI3 as a perovskite material.

[0089] Precursor solution: The MAPbI3·DMF complex obtained in Preparation Example 1 (1040 mg, 1.5 mmol) was measured and dried under reduced pressure at 60 °C and 30 mmHg for 4 hours. Then, the obtained complex was added to 1 mL of DMSO and stirred for 2 minutes to dissolve it.

[0090] The solar cell characteristics of the perovskite solar cell obtained using the above precursor solution were measured.

[0091] Perovskite solar cells A patterned transparent conductive glass substrate (FTO, 25mm × 25mm, Asahi Glass Co., Ltd., Japan) was ultrasonically cleaned for 10 minutes each using a 1% (w / w) neutral detergent aqueous solution, acetone, 2-propanol, and distilled water in that order. Finally, it was subjected to UV ozone cleaning for 15 minutes.

[0092] 1 mL of diisopropyl di(acetylacetonate) titanate (a 75% by mass solution of Ti(OiPr)₂(acac)₂, 2-propanol, Tokyo Chemical Industry Co., Ltd., Japan) was added to 39 mL of ethanol (Wako, ultra-dehydrated). The above FTO substrate (transparent electrode) was arranged on a heating plate at 450°C, and a Ti(OiPr)₂(acac)₂ solution was blown through it by spray (carrier gas: N₂, 0.5 MPa) to form a dense TiO₂ layer (approximately 30 nm). Further, the obtained substrate was immersed in an aqueous solution of 100 mL of TiCl₄ (440 μL, premium grade, Wako Pure Chemical Industries Ltd., Japan) at 70°C for 30 minutes. Then, the substrate was calcined at 500°C for 20 minutes to form a (hole) barrier layer.

[0093] A solution of approximately 190 μL (per 2.5 cm square electrode) of TiO2 paste (PST-18NR, JGC Catalysts and Chemicals Ltd.) in ethanol (paste: ethanol = 1:8 by mass) was spin-coated onto the obtained dense TiO2 layer (hole blocking layer) to form a mesoporous TiO2 layer (electron transport layer) approximately 100–150 nm thick.

[0094] The substrate, freshly treated with UV ozone and fabricated to form a mesoporous TiO2 layer (electron transport layer), was placed in a glove box. A solution was prepared by adding a mixed solvent of DMF and DMSO (Vol, 3:1) to a 1:1 molar ratio of PbI2 and MAI at a concentration of 1.5M. After adding and dissolving MAI, approximately 250 μL (per 2.5 cm square electrode) of this solution was coated onto the mesoporous TiO2 layer (electron transport layer) and spin-coated. During this process, 0.5 mL of toluene was added to obtain a transparent film (tilt for 5 seconds at 5000 rpm, spin-coat for another 5 seconds, add toluene dropwise in the last second, tilt for 5 seconds to stop). The resulting film was annealed at 40°C for 5 minutes, at 55°C for 5–30 minutes, at 75°C for 5 minutes, and then at 100°C for 30 minutes to form a flat and dense perovskite layer approximately 500 nm thick.

[0095] Hole transport material (Spiro-OMeTAD; 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene, 61.3 mg, 0.050 M), [tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tris(bis(trifluoromethanesulfonyl)imide)] (FK209; 11.3 mg, 0.0075 M), 4-tert-butylpyridine (TBP; 24.4 μL, 0.165 M, Aldrich), and lithium bis(trifluoromethanesulfonyl)imide (LITFSI; 7.6 mg, 0.027 M, Wako Pure Chemical Industries Co., Ltd.) were dissolved in 1 mL of chlorobenzene. After stirring for 30 minutes, the solution was filtered through a membrane filter, and the filtrate was spin-coated onto a perovskite layer. After annealing the obtained substrate at 70°C for 30 minutes to form a hole transport layer (approximately 200 nm), an 80 nm gold electrode is installed on the hole transport layer by vacuum evaporation to obtain a perovskite solar cell.

[0096] In addition, the preparation method of epoxy film sealing material and epoxy resin sealed perovskite solar cell test piece, as well as the determination method of viscosity and adhesion (adhesion strength) are described below.

[0097] [Preparation method of epoxy film sealant] Add 2.5 parts of CPI-300 (manufactured by San-Apro Ltd.) to 200 parts of the above-mentioned 50% anisole varnish of epoxy resin. Using a bar coater, apply the epoxy resin anisole solution onto a release PET film that has been surface-treated with a silicone-based release agent. Dry the PET film coated with the epoxy resin adhesive using a dryer at 100°C for 10 minutes to obtain an epoxy film-like sealant (adhesive) with an adhesive layer of 20 μm.

[0098] [Preparation method of epoxy resin sealed perovskite solar cell experimental piece] Regarding the epoxy resin-sealed perovskite solar cell test piece of the present invention, the above-mentioned epoxy film-like sealing material was vacuum-laminated on the perovskite solar cell test piece at 80 or 100°C for 60 seconds, and then vacuum-laminated at room temperature (25°C) at 460 mW / cm². 2 3000mJ / cm 2 Irradiation with a 365nm UV-LED yielded an epoxy resin-sealed perovskite solar cell test piece.

[0099] [Viscosity Measurement Methods] The viscosity of the varnish (epoxy anisole solution) obtained in the synthesis example was measured using an Orthocrite viscometer in a constant temperature water bath at 25°C.

[0100] [Adhesion strength] The epoxy resin compositions (epoxy anisole solution) obtained in Synthetic Examples 1-3 were dissolved in anisole solvent to a solid content of 50%, and coated onto a PET film coated with fluorinated silicone at a thickness of 25 μm using a rod coater. The solvent was dried at 100°C for 10 minutes to obtain an adhesive layer with a thickness of 20 μm. This adhesive layer was then attached to a 5 mm × 5 mm film at 100°C for 60 seconds. A 725μm quartz sheet was then sandwiched between 30mm*75mm*2mm glass test pieces in a quartz-epoxy-glass layer configuration, and subjected to a temperature of 100℃ and 6kgf / cm². 2 The pressing was performed under conditions of 60 seconds at room temperature (25℃) with a pressure of 460mW / cm. 2 3000mJ / cm 2 The epoxy resin layer was cured by irradiation with a 365nm UV-LED. This process was used to create adhesive test pieces. The shear bond strength was then measured using a Dage4000 adhesive testing machine manufactured by Dage Corporation at a speed of 0.5 mm / min.

[0101] [JV Feature Evaluation Method] The photoelectric conversion characteristics of the perovskite solar cells in the examples and comparative examples were measured using a method based on the method for measuring the output of crystalline solar cell units according to JIS C 8913:2005. An AM1.5G air mass filter was integrated into a solar simulator (manufactured by OTETO-SUNIII, Bunkoukeiki Co., Ltd.), and the light intensity of the light source used for measurement was adjusted to 100 mW / cm² using the reference solar cell unit. 2 . In actual measurements, one side is aligned to ensure the measured area is 0.1 cm². 2 The covered solar cell elements were illuminated, and the JV curve characteristics were measured using a SourceMeter (Model 2400, manufactured by Keithley Instruments). Based on the results, the short-circuit current (Jsc), open-circuit voltage (Voc), curve factor (FF), series resistance (Rs), and parallel resistance (Rsh) were derived. Furthermore, the photoelectric conversion efficiency (PCE) was calculated using the following mathematical formula. The initial PCE was calculated for the aforementioned epoxy film sealing material, and the post-sealing PCE was calculated for the aforementioned epoxy resin-sealed perovskite solar cell test piece. PCE(%) = (Jsc(mA / cm)) 2 )×Voc(V)×FF / 100(mW / cm 2 ))×100

[0102] The results are shown in Table 1.

[0103] [Table 1]

[0104] In Examples 1-3, which used the film-like sealing material obtained from the adhesive composition of the present invention (the varnishes of Synthetic Examples 2 and 3), the composition had low viscosity, could be cured at low temperatures, and exhibited excellent adhesion, maintaining the power generation performance of the perovskite solar cell before and after sealing. On the other hand, for Comparative Example 1, which is not part of the present invention and has a (total number of moles of epoxy groups) / (number of moles of acid anhydride) ratio of less than 1.30 and a bifunctional epoxy resin ratio of greater than 0.15, the composition had high viscosity, poor adhesion, and a significant reduction in the power generation performance of the perovskite solar cell after sealing.

[0105] This manual includes the following solutions. [1]: An adhesive composition comprising: (A) a reaction product of a bifunctional epoxy resin of general formula (2), a trifunctional epoxy resin of general formula (3), and a saturated anhydride of general formula (4); (B) a UV-sensitive reaction initiator; and (C) a diluent, wherein the adhesive composition is characterized in that... The component (A) is a compound represented by the following general formula (1). The amounts of the difunctional epoxy resin, the trifunctional or higher epoxy resin, and the saturated anhydride are such that the ratio of the total molar number of epoxy groups of the difunctional epoxy resin and the trifunctional or higher epoxy resin to the molar number of the saturated anhydride is 1.30 to 3.00, and the molar number of the difunctional epoxy resin is such that the ratio of the molar number of the difunctional epoxy resin and the trifunctional or higher epoxy resin to the total molar number of the difunctional epoxy resin and the trifunctional or higher epoxy resin is 0.001 to 0.15. In the formula, A is a saturated divalent hydrocarbon group; B is a group independently represented by general formula (1a) or general formula (1b); R2 is a substituted or unsubstituted divalent organic group, including aliphatic hydrocarbon groups, aromatic rings or heterocycles; R3 is a substituted or unsubstituted trivalent or higher organic group, including aliphatic hydrocarbon groups, aromatic rings or heterocycles; Z is a single bond or oxygen atom independently; k is an integer greater than 2; * represents an atomic bond; the order of repeating unit 1 and repeating unit m is arbitrary in the formula. In the formula, R2 and Z are the same as those mentioned above. In the formula, R3, Z, and k are the same as those mentioned above. In the formula, A is the same as the A mentioned above. [2]: The adhesive composition according to [1] is characterized in that the reaction product is a polymer formed by polymerizing the difunctional epoxy resin, the epoxy resin with more than three functions and the saturated anhydride, wherein the weight average molecular weight of the polymer is 2000 to 20000. [3]: The adhesive composition according to [1] or [2] is characterized in that it further contains the reaction product of general formula (5) as the (A) component, which is obtained by reacting an alkoxysilane compound of general formula (6) or a partial hydrolysate thereof with a compound of general formula (1). In the formula, A, R2, R3, Z, k, and * are the same as A, R2, R3, Z, k, and * above; B' is each independently a group shown in general formula (5a) or general formula (5b); Z' is each independently a group of R4(OR5)2Si- or a group of a partially hydrolyzed alkoxysilane compound from general formula (6); R4 is a monovalent organic group containing vinyl, styryl, acryloyl, methacryloyl, amino, mercapto, urea, or isocyanate groups; and R5 is a monovalent organic group containing methyl, ethyl, propyl, or isopropyl groups. [4]: The adhesive composition according to any one of [1] to [3] is characterized in that the bifunctional epoxy resin is a BisA type epoxy resin represented by the following general formula (2'), the epoxy resin with more than three functions is a triazine cyclic trifunctional epoxy resin represented by the following general formula (3'), and the saturated anhydride is a saturated hydrocarbon anhydride represented by the following general formula (4'). In the formula, n is an integer greater than or equal to 1. [5]: A film-like sealing material formed from the dried solid of any one of the adhesive compositions described in [1] to [4]. [6]: The membrane sealing material according to [5] is characterized in that the membrane sealing material further comprises a residual solvent, the residual solvent being dimethylformamide and / or dimethyl sulfoxide, the residual amount of the residual solvent in the membrane sealing material per unit mass being less than 5000 ppm.

[0106] Furthermore, this invention is not limited to the above-described embodiments. The above embodiments are illustrative examples, and any technical solutions having a substantially identical structure and achieving the same effect as the technical concept described in the claims of this invention are included within the scope of protection of this invention.

Claims

1. An adhesive composition comprising: (A) a reaction product of a bifunctional epoxy resin of general formula (2), a trifunctional or higher epoxy resin of general formula (3), and a saturated anhydride of general formula (4); (B) a UV-sensitive reaction initiator; and (C) a diluent, wherein the adhesive composition is characterized in that, The component (A) is a compound represented by general formula (1) below, wherein the adhesive composition further contains a reaction product represented by general formula (5) obtained by reacting an alkoxysilane compound represented by general formula (6) below or a partial hydrolysate thereof with the compound represented by general formula (1). , In the formula, A is a saturated divalent hydrocarbon group; B is a group independently represented by general formula (1a) or general formula (1b); R2 is a substituted or unsubstituted divalent organic group, including aliphatic hydrocarbon group, aromatic ring or heterocycle; R3 is a substituted or unsubstituted trivalent or higher organic group, including aliphatic hydrocarbon group, aromatic ring or heterocycle; Z is a single bond or oxygen atom independently; k is an integer greater than 2; The connection point is indicated; the order of repeating element l and repeating element m in the formula is arbitrary. , In the formula, R2 and Z are the same as those mentioned above. , In the formula, R3, Z, and k are the same as those mentioned above. , In the formula, A is the same as the A mentioned above. , , In the formula, A, R2, R3, Z, k, With the above A, R2, R3, Z, k, The same; B' is each independently a group represented by general formula (5a) or general formula (5b); Z' is each independently a group of R4(OR5)2Si-, or a group of a partially hydrolyzed alkoxysilane compound of general formula (6); R4 is a monovalent organic group containing vinyl, styryl, acryloyl, methacryloyl, amino, mercapto, urea, or isocyanate groups, and R5 is a monovalent organic group containing methyl, ethyl, propyl, or isopropyl groups. The amounts of the difunctional epoxy resin, the trifunctional or higher epoxy resin, and the saturated anhydride are such that the ratio of the total molar number of epoxy groups of the difunctional epoxy resin and the trifunctional or higher epoxy resin to the molar number of the saturated anhydride is 1.30 to 3.00, and the molar number of the difunctional epoxy resin is such that the ratio of the total molar number of the difunctional epoxy resin and the trifunctional or higher epoxy resin is 0.069 to 0.

15. The bifunctional epoxy resin is a BisA type epoxy resin represented by the following general formula (2'), the epoxy resin with more than three functions is a triazine cyclic trifunctional epoxy resin represented by the following general formula (3'), and the saturated acid anhydride is a saturated hydrocarbon acid anhydride represented by the following general formula (4'). , In the formula, n is an integer greater than or equal to 1. , 。 2. The adhesive composition according to claim 1, characterized in that, The reaction product is a polymer formed by polymerizing the difunctional epoxy resin, the epoxy resin with more than three functions, and the saturated acid anhydride. The weight-average molecular weight of the polymer is 2000 to 20000, which is the weight-average molecular weight converted from standard polystyrene as determined by GPC.

3. A film-like sealing material comprising the dried product of the adhesive composition of claim 1 or 2.

4. The film-like sealing material according to claim 3, characterized in that, The membrane sealing material further comprises a residual solvent, which is dimethylformamide and / or dimethyl sulfoxide, and the residual amount of the residual solvent in each unit mass of the membrane sealing material is less than 5000 ppm.

Citation Information

Patent Citations

  • Encapsulant, encapsulation sheet, electronic device, and perovskite solar cell

    JP2021089946A

  • Ultraviolet curing removable adhesive composition and adhesive sheet using the same

    CN102177214A

  • Adhesive composition and sheet for forming semiconductor wafer-protective film

    CN102191005A